Antineoplastic effects of auranofin in human pancreatic adenocarcinoma preclinical models - Mayrim V. Rios Perez; David Roife; Bingbing Dai; Michael Pratt; Ryszard Dobrowolski; Ya'an Kang; Xinqun Li; Jithesh J. Augustine; Rafal Zielinski; Waldemar Priebe; Jason B. Fleming (Surgery Open Science, 2019)
Background: Auranofin, a Food and Drug Administration–approved anti-rheumatic agent with anticancer properties for lung and ovarian cancer, has never been studied for pancreatic cancer. We hypothesize that auranofin may prevent pancreatic ductal adenocarcinoma progression by inhibition of Txnrd1 and HIF-1α. Methods: In vitro sensitivity of human pancreatic ductal adenocarcinoma cell lines was determined based on IC50. Western blot assays were used to interrogate mechanisms of apoptosis and resistance. Ex vivo live tissue slice assays of xenografts allowed for testing of a larger number of PDX samples with high efficiency. In vivo pancreatic ductal adenocarcinoma orthotopic mouse models using MiaPaCa-2 Luc + cells were designed to determine optimal dose and antitumor effect. Results: We found that 10 of 15 tested pancreatic ductal adenocarcinoma cell lines were sensitive to auranofin based on IC50s below 5 μmol/L. Ex vivo tissue growth inhibition greater than 44% was observed for 13 PDX tissue cases treated with 10 μmol/L auranofin. High Txnrd1 expression was observed for resistant cell lines. In vivo studies showed 15 mg/kg IP as the optimal dose with absence of gross solid organ metastasis up to 13 weeks post-treatment (median survival 8 and 12 weeks, respectively; P = .0953). Conclusions: We have demonstrated that auranofin prevents pancreatic ductal adenocarcinoma progression using multiple models. Our study suggests inhibition of Txnrd1 and HIF-1α as possible mechanisms of action, and Txnrd1 as a biomarker of resistance. Based on these data, an off-label Phase 0 clinical trial with this FDA-approved drug should be considered for patients with pancreatic cancer.